IFLA MENA Regional Office : 2024 Highlights and Future Plans - Eiman Alshamari (21694012) (2025)
This presentation highlights the key achievements and future plans of the IFLA MENA Regional Office (IFLA MENA RO) for 2024, with a focus on capacity-building programs, regional and international partnerships, and the development of libraries across the Middle East and North Africa. It also covers initiatives that support emerging librarians and foster collaboration and knowledge exchange among libraries in the region. Other Information Presentation was given at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda